Visual arts, representations and interventions in contemporary China : urbanized interface - Valjakka, Minna; Wang, Meiqin, 1974- (Asian cities (Amsterdam, Netherlands), 2018)
This edited volume provides a multifaceted investigation of the dynamic interrelations between visual arts and urbanization in contemporary Mainland China with a focus on unseen representations and urban interventions brought about by the transformations of the urban space and the various problems associated with it. Through a wide range of illuminating case studies, the authors demonstrate how innovative artistic and creative practices initiated by various stakeholders not only raise critical awareness on socio-political issues of Chinese urbanization but also actively reshape the urban living spaces. The formation of new collaborations, agencies, aesthetics and cultural production sites facilitate diverse forms of cultural activism as they challenge the dominant ways of interpreting social changes and encourage civic participation in the production of alternative meanings in and of the city. Their significance lies in their potential to question current values and power structures as well as to foster new subjectivities for disparate individuals and social groups.